Gulian Verplanck indentures - Verplanck, Gulian
Indenture (1728 August 15) between Verplanck and Henry Beekman and indenture (1750) between Verplanck and John Montross documenting land transactions in Dutchess County, N.Y.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Beekman, Henry, -- 1688-1776.; Montross, John; Deeds -- New York (State) -- Dutchess County; Landowners